The Incidence of Mitral Valve Prolapse and Mitral Valve Regurgitation in Patient with Secundum Atrial Septal Defect - Ni Made Elva Mayasari; Dyah Wulan Anggrahini; Hasanah Mumpuni; Lucia Krisdinarti (ACI (Acta Cardiologia Indonesiana), 2015)
Background: Association between secundum atrial septal defect (ASD) and mitral valve disease has been recognized for many years. Noninvasive studies indicate a high incidence of mitral valve prolapse (37-70 percent) in these patients. Change of left ventricular geometry in atrial septal defect had been showed were associated with degree of mitral valve prolapse. This study delineates the incidence of mitral valve prolaps and mitral regurgitation in adult patients with secundum atrial septal defect and association with age at onset and size defect. Method: This study was a substudy from ASD registry in Dr. Sardjito General Hospital. The records of 103 adult patients ranged in age from 17 to 76 years old, with an average of 36 years old, and consisted of 16 men and 87 women who had secundum atrial septal defects demonstrated by crosssectional echocardiography between july 2012 until july 2013. Echocardiographic examinations were performed with the patient in the supine position. The echocardiograph was a Vivid 7. The mitral valve apparatus and mitral regurgitation was examined with long axis images, short axis image and apical four chamber view. Result: Mitral valve prolapse was observed in 76% patients with secundum atrial septal defect. Prolaps of anterior mitral leafl et (AML) in age group younger than 35 years and older than 36 years are 38,6% and 61,4% respectively. The incidence of mitral regurgitation was 43%. Severity varianceof mitral regurgitation were 31,7% mild, 7,7% moderate and 2,9% severe. Mitral regurgitation in patient with prolapse AML was 56.4%. None of the patients without mitral valve prolapse had mitral regurgitation.In patient with size defect more than 2 cm, the proportion of prolapse of AML and mitral regurgitation was higher as compared with patient with size defect less than 2 cm. Conclusion: Incidence of mitral valve prolaps and mitral regurgitation are high in patient with atrial septal defect and increase with onset of age. Patients with larger size defect had a greater likelihood of mitral prolapse and mitral regurgitation. Onset of age and size defect might be associated with magnitude of the shunt and abnormal ventricular geometry.Keywords: secundum atrial septal defect, mitral valve prolaps, mitral regurgitation